2021
DOI: 10.3390/jpm11070629
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Mandible from Conventional Methods to Deep Learning—A Review

Abstract: Medical imaging techniques, such as (cone beam) computed tomography and magnetic resonance imaging, have proven to be a valuable component for oral and maxillofacial surgery (OMFS). Accurate segmentation of the mandible from head and neck (H&N) scans is an important step in order to build a personalized 3D digital mandible model for 3D printing and treatment planning of OMFS. Segmented mandible structures are used to effectively visualize the mandible volumes and to evaluate particular mandible properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 110 publications
(145 reference statements)
0
21
0
1
Order By: Relevance
“…The development of semantic segmentation AI models for medical image analysis is a field of study that is becoming increasingly widespread, especially for radiologic imaging ( 43 45 ). Conversely, the exploitation of these algorithms to investigate videoendoscopic images represents a sphere of research less explored in the literature, as demonstrated by the lack of proper terminology to indicate such a field of interest before our first proposal to identify it as “Videomics” ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of semantic segmentation AI models for medical image analysis is a field of study that is becoming increasingly widespread, especially for radiologic imaging ( 43 45 ). Conversely, the exploitation of these algorithms to investigate videoendoscopic images represents a sphere of research less explored in the literature, as demonstrated by the lack of proper terminology to indicate such a field of interest before our first proposal to identify it as “Videomics” ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…20,37 A detailed discussion is beyond the scope of this article; however, segmentation can be performed manually, using automated/semi-automated rule-based techniques, machine learned algorithms, or a combination of the three. [38][39][40][41][42][43][44][45][46][47] Performing manual segmentation is very timeconsuming, as the user is required to mark (with a paintbrush or a lasso) each slice of the image stack, which can contain hundreds of slices. 48 To speed up the process, various automated segmentation algorithms exist with the most common being thresholding, edge detection, and region growing.…”
Section: Medical Image Segmentationmentioning
confidence: 99%
“…Recently, machine-learning techniques have been used for data analysis in a variety of fields, including the education [16,17], energy [18,19], environmental [20,21], medical [22][23][24], and security [25][26][27] fields, to assist professionals in saving time and effort because machine learning can effectively discover nonlinear relationships between dependent and independent variables in numerical datasets. To address classification problems in the medical field, Shailaja et al [28] presented various machine-learning techniques, such as the support vector machine, naive Bayes classification, k-nearest neighbors, and others, to predict various diseases, such as heart disease, breast cancer, diabetes, and thyroid disease.…”
Section: Introductionmentioning
confidence: 99%